A New Bioassay for the Detection of Paralytic and Amnesic Biotoxins Based on Motor Behavior Impairments of Zebrafish Larvae - Ortiz-Cisternas, F (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The global concern about the increase of harmful algal bloom events and the possible impacts on food safety and aquatic ecosystems presents the necessity for the development of more accessible techniques for biotoxin detection for screening purposes. Considering the numerous advantages that zebrafish present as a biological model and particularly as a toxicants sentinel, we designed a sensitive and accessible test to determine the activity of paralytic and amnesic biotoxins using zebrafish larvae immersion. The ZebraBioTox bioassay is based on the automated recording of larval locomotor activity using an IR microbeam locomotion detector, and manual assessment of four complementary responses under a simple stereoscope: survival, periocular edema, body balance, and touch response. This 24 h acute static bioassay was set up in 96-well microplates using 5 dpf zebrafish larvae. For paralytic toxins, a significant decrease in locomotor activity and touch response of the larvae was detected, allowing a detection threshold of 0.1–0.2 µg/mL STXeq. In the case of the amnesic toxin the effect was reversed, detecting hyperactivity with a detection threshold of 10 µg/mL domoic acid. We propose that this assay might be used as a complementary tool for environmental safety monitoring. © 2023 by the authors.
Keywords: zebrafish; bioassay; locomotor activity; biotoxin; saxitoxin; domoic acid; neurotoxin; HAB; harmful algal bloom; ZebraBioTox